Complaint Severity and Resolution Time in a Hospital Outpatient Department Digital Complaint Management System: A Retrospective Observational Study - Michelly; Mirachel; Puspita Angelina; Thoe Isabella Roseline Pramana Putri (Riviera Publishing, 2026)
Efficient management of patient complaints is a cornerstone of healthcare quality assurance. This study aimed to determine the association between complaint severity level and overall turnaround time (TAT) in a hospital OPD digital complaint management system. A retrospective observational study was conducted using a balanced sample of 96 OPD complaint tickets (24 per severity group, S1–S4) extracted from a tertiary hospital digital complaint system. The primary outcome was Overall TAT (minutes). Board TAT and complaint type were included as secondary variables. Normality was assessed using the Shapiro–Wilk test. The Kruskal–Wallis H test with Bonferroni post-hoc correction was applied for between-group comparisons. Pearson correlation examined bivariate associations. Multiple linear regression was performed to assess the simultaneous predictive value of severity group, Board TAT, and complaint type on Overall TAT. The sample comprised 58 males (60.4%) and 38 females (39.6%). Overall TAT differed significantly across severity groups (H = 55.344, p<0.001), with S1 having the highest median TAT (27.07 min) and S4 the lowest (0.00 min). Board TAT also differed significantly across groups (H = 58.275, p<0.001), with significant pairwise differences between S1 vs S2 (p = 0.010) and S1 vs S4 (p = 0.003). Pearson correlation revealed a significant inverse association between severity group and Overall TAT (r = -0.215, p = 0.018). The multivariable regression model was not statistically significant (F(3,92) = 1.747, p = 0.163; R² = 0.054), suggesting that additional unmeasured factors contribute to resolution time. Complaint severity is significantly associated with Overall TAT at the bivariate level, with higher-urgency complaints demonstrating longer resolution times.